Nimbolide targeting SIRT1 mitigates intervertebral disc degeneration by reprogramming cholesterol metabolism and inhibiting inflammatory signaling - Yun Teng; Yixue Huang; Hao Yu; Cenhao Wu; Qi Yan; Yingjie Wang; Ming Yang; Haifeng Xie; Tianyi Wu; Huilin Yang; Jun Zou (Acta Pharmaceutica Sinica B, 2023)
Inflammation, abnormal cholesterol metabolism, and macrophage infiltration are involved in the destruction of the extracellular matrix of the nucleus pulposus (NP), culminating in intervertebral disc degeneration (IDD). Whether nimbolide (Nim), a natural extract, can alleviate IDD is unclear. In this study, we demonstrated that Nim promotes cholesterol efflux and inhibits the activation of the nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways by activating sirtuin 1 (SIRT1) in nucleus pulposus cells (NPCs) during inflammation. Thus, Nim balanced matrix anabolism and catabolism of NPCs. However, the inhibition of SIRT1 significantly attenuated the effects of Nim. We also found that Nim promoted the expression of SIRT1 in RAW 264.7, which enhanced the proportion of M2 macrophages by facilitating cholesterol homeostasis reprogramming and impeded M1-like macrophages polarization by blocking the activation of inflammatory signaling. Based on these results, Nim can improve the microenvironment and facilitate matrix metabolism equilibrium in NPCs. Furthermore, in vivo treatment with Nim delayed IDD progression by boosting SIRT1 expression, modulating macrophage polarization and preserving the extracellular matrix. In conclusion, Nim may represent a novel therapeutic strategy for treating IDD.